2015
DOI: 10.1071/ma15066
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of human cytomegalovirus via breastmilk and potential risks to very preterm infants

Abstract: Breastfeeding has clear short-term benefits for the baby1. Additionally, based on a prospective long-term cohort study from Brazil, breastfeeding is associated with improved IQ scores and increased educational attainment 30 years later2. During lactation, mother-to-infant transmission of viral infections like HIV, hepatitis B (HBV), and human cytomegalovirus (HCMV), may occur. The article presented here will focus on the dynamics of HCMV shedding into breastmilk, describe the short- and long-term risks of HCMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Only one seropositive mother failed to yield any evidence for viral reactivation during the observation period. This is not unusual, because it has been reported that not exactly 100% of seropositive breastfeeding mothers shed the virus into milk (9,12,30).…”
Section: Discussionmentioning
confidence: 93%
“…Only one seropositive mother failed to yield any evidence for viral reactivation during the observation period. This is not unusual, because it has been reported that not exactly 100% of seropositive breastfeeding mothers shed the virus into milk (9,12,30).…”
Section: Discussionmentioning
confidence: 93%